2015
DOI: 10.2320/matertrans.m2014440
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Run-in-Stage Wear Behavior and Contact Mechanics of Metal-on-Metal Hip Joint Bearings with Different Radial Clearances

Abstract: We systematically elucidate the effects of radial clearance on the wear behavior of hip joint prostheses bearings during run-in-stage. The results indicated that bearings with smaller radial clearances exhibited lower wear rate and less abrasive wear characterized by mild surface roughness and sphericity. The contact mechanics and lubrication regime of MOM bearings with different radial clearances were also analyzed, indicating that bearings with radial clearance of ³20 µm was more beneficial for small contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Nickel-based and cobalt-based metal alloys are frequently used in dentistry for prosthodontic restorations due to their advantageous characteristics [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Nickel in an alloy can cause allergic reactions and toxicity, according to some studies [ 9 , 10 , 11 , 12 , 13 ], but others report very different results and conclusions [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nickel-based and cobalt-based metal alloys are frequently used in dentistry for prosthodontic restorations due to their advantageous characteristics [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Nickel in an alloy can cause allergic reactions and toxicity, according to some studies [ 9 , 10 , 11 , 12 , 13 ], but others report very different results and conclusions [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The International Organization for Standardization (ISO) provided researchers with several rules, based on which the in vitro evaluation of the newly-designed artificial joints would be performed before clinical applications. However, it has been reported that the standard only offers the loading profiles and motion tracks under the normal walking conditions [11,12]. Bowsher and Shelton [13] once investigated the differences of the peak loads among walking, jogging, and stumbling, and found that the peak load during stumbling was two times more than that under the normal walking condition.…”
Section: Introductionmentioning
confidence: 99%